2015
DOI: 10.1186/s12872-015-0017-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms behind progressing chronic inflammatory dilated cardiomyopathy

Abstract: BackgroundInflammatory dilated cardiomyopathy (iDCM) is a common debilitating disease with poor prognosis that often leads to heart failure and may require heart transplantation. The aim of this study was to evaluate sera and biopsy samples from chronic iDCM patients, and to investigate molecular mechanism associated with left ventricular remodeling and disease progression in order to improve therapeutic intervention.MethodsPatients were divided into inflammatory and non-inflammatory DCM groups according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 41 publications
0
18
2
Order By: Relevance
“…These observations agree with the polymorphisms analyzed in patients with idiopathic dilated cardiomyopathy (IDCM) that relates to TNF, IL-6, and CRP profile. A recent study shows that a rough increase in serum IL-6 is incidental with chronic IDCM [82].…”
Section: Interleukin-6mentioning
confidence: 99%
“…These observations agree with the polymorphisms analyzed in patients with idiopathic dilated cardiomyopathy (IDCM) that relates to TNF, IL-6, and CRP profile. A recent study shows that a rough increase in serum IL-6 is incidental with chronic IDCM [82].…”
Section: Interleukin-6mentioning
confidence: 99%
“…Inflammation is a natural biological process that occurs during times of infection or wound healing and is self-limiting which is hence called acute inflammation. During chronic inflammation this self-limiting process is deregulated and can contribute to a number of diseases including: Alzheimer's [ 6 ], cardiomyopathy [ 7 ], osteoarthritis [ 8 ], inflammatory bowel disease (IBD) [ 9 ], and numerous types of cancers including breast [ 10 12 ]. Specifically, chronic inflammation has been associated with cancer initiation and progression [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous epidemiological studies have identified cardiac inflammation and insulin resistance as independent risk factors for the development of heart failure 11,17,56,57 . However, little is known about the relationship between these factors in terms of the mechanism involved in cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%